Causal inference in genetic epidemiology: Mendelian randomization and beyond - Fischer, Krista (Henry Stewart Talks, 2017)
Definitions of causal effect, Causal graphs, confounding and adjustment, Instrumental variables estimation, Mendelian randomization, Association structure with one genotype and two phenotypes